Polymerization-incompetent uromodulin in the pregnant stroke-prone spontaneously hypertensive rat - Mary, Sheon; Small, Heather Yvonne; Siwy, Justyna; Mullen, William; Giri, Ashok; Delles, Christian (Hypertension, 2017)
The kidney is centrally involved in blood pressure regulation and undergoes extensive changes during pregnancy. Hypertension during pregnancy may result in an altered urinary peptidome that could be used to indicate new targets of therapeutic or diagnostic interest. The stroke-prone spontaneously hypertensive rat (SHRSP) is a model of maternal chronic hypertension. Capillary electrophoresis-mass spectrometry was conducted to interrogate the urinary peptidome in SHRSP and the control Wistar-Kyoto strain at three time points: prepregnancy and gestational days 12 and 18. The comparison within and between the Wistar-Kyoto and SHRSP peptidome at all time points detected 123 differentially expressed peptides (fold change >1.5; P<0.05). Sequencing of these peptides identified fragments of collagen a-chains, albumin, prothrombin, actin, serpin A3K, proepidermal growth factor, and uromodulin. Uromodulin peptides showed a pregnancy-specific alteration in SHRSP with a 7.8-fold (P<0.01) and 8.8-fold (P<0.05) increase at gestational days 12 and 18, respectively, relative to the Wistar-Kyoto. Further investigation revealed that these peptides belonged to the polymerization-inhibitory region of uromodulin. Two forms of uromodulin (polymerization competent and polymerization incompetent) were found in urine from both Wistar-Kyoto and SHRSP, where the polymerizationincompetent form was increased in a pregnancy-specific manner in SHRSP. Nifedipine-treated pregnant SHRSP showed only polymerization-competent uromodulin, indicating that calcium may be mechanistically involved in uromodulin polymerization. This study highlights, for the first time, a potential role of uromodulin and its polymerization in hypertensive pregnancy.
Keywords: Hypertension; Kidney; Nifedipine; pregnancy; uromodulin